Relevansi Nilai Dividend Yield dan Price Earnings Ratio (PER) dalam Penilaian Harga Saham Bagi Perusahaan yang Mengalami Pertumbuhan (Studi pada Perusahaan Manufaktur di BEJ Tahun 2001-2005) - I Ketut Jati; Ni Luh Supadmi (BISMA (Bisnis dan Manajemen), 2018)
The aim of this research are developed and tested model of market appraiser with first prediction is a equities value.It was  a  function of  book value, rented earning  and deviden . This function  broaded  using proction IOS of company growth level  to know  value relevation of devidend yield value and price earning ratio (PER) in orther to appariser stock price.Further more , model which used in this research  are devidend and rented earning  already reflection of using devidend yield and price earning ratio by stock market agentIn addition, the main problem of this research was, How is a relevantion between company growth value, devidend yield, and PER in orther to appraiser stock price?. How is company growth has influnce  toward relevantion  of dividend yield value  and PER in orther to appraiser stock price . The aim of this research is to know are there any influence of relevantion between company growth value , dividend yield and PER in orther to appraiser stock price and to know are there any influence  of company growth  toward relevantion value  dividence yield  and PER in orther to appraiser stock price .This research using proposive sampling technique and respondance are manufacture company  listed in Jakarta stock exchange during 2001 2005. Data analysis using multiple regretion technique with price and model return . To get  just one value so this research  using factor analysis because IOS  as a proction company growth .Base on price models, result analysis show company growth , devidend yield and PER  , all together  and partial have relation  or relevantion with stock price.Relevantion of devidend yield value  and PER in apparaiser stock price has not influence  of company growth level . In other hand,  model return show that company growth, devidend yield and PER  has not value relevantion in  appraiser stock price . It has related with stale component and accounting recognition lag which as application in return modelIn conclusion, using alpha 5%, company growth, devidend yield  and PER  has relevantion value in  appraiser stock price . But,company growth   has not  a basic of relevantion devidend yield value  and PER  in orther to appraiser stock price for stock market agent . PER for appraiser stock price with stock agent  in stock exchange market in Jakarta during 2001 2005. Disclosure of company growth with any eforts from emitance be desirable that being relevant information for any capital stock market i Indonesia.